Aktivitas Belajar Siswa pada Pembelajaran Model Discovery-Inquiry Berbantuan Mind Mapping di SD - Alvinita Lutvia; Sulton Sulton; Lia Yuliati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This research aims to determine the application of the discovery-inquiry learning model assisted by mind mapping to improve student learning activities in elementary school. The type of research used is Classroom Action Research qualitative descriptive data analysis methods. Students of class IV.2 in SDN 3 Besuki Situbondo consisted of 32 students with 14 males and 18 females who were chosen as research subjects. Data collection using observation techniques. Based on the results, it is concluded that the discovery-inquiry learning model assisted by mind mapping may improve student learning activities. The activities during the learning process with the discovery-inquiry model assisted by mind mapping facilitate students to formulate problems, formulate hypotheses, collect data, test hypotheses, and formulate conclusions by creating material mind mapping independently so that students’ activities are increased and varied.Abstrak: Penelitian ini bertujuan mengetahui penerapan model pembelajaran discovery-inquiry berbantuan mind mapping dalam meningkatkan aktivitas belajar siswa di sekolah dasar. Jenis penelitian ini adalah Penelitian Tindakan Kelas dengan metode analisis data deskriptif kualitatif. Siswa kelas IV.2 SDN 3 Besuki Situbondo berjumlah 32 siswa, terdiri dari 18 siswa perempuan dan 14 siswa laki-laki yang dipilih sebagai subjek penelitian. Pengumpulan data aktivitas belajar siswa menggunakan teknik observasi. Berdasarkan hasil penelitian disimpulkan bahwa model pembelajaran discovery-inquiry berbantuan mind mapping dapat meningkatkan aktivitas belajar siswa. Kegiatan selama pembelajaran dengan model discovery-inquiry berbantuan mind mapping dapat memfasilitasi siswa merumuskan masalah, merumuskan hipotesis, mengumpulkan data, menguji hipotesis, dan merumuskan kesimpulan dengan membuat mind mapping materi secara mandiri sehingga membuat aktivitas siswa semakin meningkat dan bervariasi.